The nexus between education, economic growth and environmental quality: empirical evidence from Egypt and Morocco. (7th May 2021) - Farag, Noran; Ibrahiem, Dalia M.; Sayed, Samy El
This study examines the relationships between education, economic growth and environmental quality in Egypt and Morocco. Auto regressive distributed lag (ARDL) bound testing approach over the period 1990 to 2017 is used to investigate these relationships. The empirical findings show that the variables are cointegrated demonstrating that long-run relationship exists among those variables. In the short run, education has positive effects on amounts of carbon dioxide emissions in both countries. Though, in the long run, increasing literacy rates might lead to improve environmental quality. As for the effect of the economic growth, the results showed that carbon dioxide emissions increase as the GDP grows in both the long and short run for the case of Egypt but in Morocco, the GDP growth has no effect on the CO2 emissions.